Probing the anomalous γγγZ coupling at the LHC with proton tagging - Baldenegro, C.; Fichet, S. [UNESP]; von Gersdorff, G.; Royon, C. (Springer Nature, 2017)
The sensitivities to the anomalous quartic gauge boson coupling γγγZ are estimated via γZ production with intact protons in the forward region at the LHC. Proton tagging proves to be a powerful tool to suppress the background, which allows consideration of the hadronic decays of the Z boson in addition to the leptonic ones. We discuss the discovery potential for an integrated luminosity of 300 fb−1 and 3000 fb−1. The sensitivity we obtain at 300 fb−1 goes beyond the one expected from LHC bounds on the Z → γγγ decay by about three orders of magnitude. The γZ channel provides important discriminatory information with respect to the exclusive γγ channel, as many particles beyond the Standard Model (such as a radion or Kaluza Klein gravitons) predict a signal in the latter but not the former.
Keywords: Phenomenology of Large extra dimensions